1997
DOI: 10.1200/jco.1997.15.1.330
|View full text |Cite
|
Sign up to set email alerts
|

Trading treatment toxicity for survival in locally advanced non-small cell lung cancer.

Abstract: There is great interindividual variability in willingness to accept aggressive treatments for locally advanced NSCLC. When choosing NSCLC treatment, each patient should be provided with comprehensive information about the options so that he or she may express his or her preferences should he or she wish to participate in the decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
89
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 24 publications
9
89
0
1
Order By: Relevance
“…In contrast to the lack of studies on treatment choice, several studies have been performed on the nature and background of treatment preference (Cassileth et al, 1980;McNeil et al, 1982;Llewellyn-Thomas et al, 1995;Flood et al, 1996;Brundage et al, 1997;Mazur and Hickam, 1997;Lindley et al, 1998;Silvestri et al, 1998;Stalmeier and Bezembinder, 1999;Stiggelbout and de Haes, 2001). In the literature, the patient's preference for treatment is seen and used as an indication for their actual treatment choice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the lack of studies on treatment choice, several studies have been performed on the nature and background of treatment preference (Cassileth et al, 1980;McNeil et al, 1982;Llewellyn-Thomas et al, 1995;Flood et al, 1996;Brundage et al, 1997;Mazur and Hickam, 1997;Lindley et al, 1998;Silvestri et al, 1998;Stalmeier and Bezembinder, 1999;Stiggelbout and de Haes, 2001). In the literature, the patient's preference for treatment is seen and used as an indication for their actual treatment choice.…”
mentioning
confidence: 99%
“…Firstly, framing influences treatment preferences, that is, whether outcomes are presented in terms of survival or in terms of death, and whether or not medical uncertainties are explicitly mentioned (McQuellon et al, 1995;Flood et al, 1996;Mazur and Hickam, 1997;O'Connor, 1998). Secondly, disease experience seems to be of influence: patients are more willing than the general public or medical staff to accept toxic treatment (Slevin et al, 1990;Degner and Sloan, 1992;Brundage et al, 1997). Thirdly, various demographic variables such as age, living with others and having children may also have an impact on treatment preferences of patients (Kiebert et al, 1994;Unic et al, 1998).…”
mentioning
confidence: 99%
“…The best solution to this trade-off between a survival benefit and toxicity is perplexing to patients, and difficult for physicians to estimate on behalf of a patient. 6 When high-quality clinical data are available from controlled clinical trials, the quality-adjusted time without symptoms or toxicity (Q-TWiST) approach can provide a nomogram and assist patients and physicians in making difficult treatment decisions. [7][8][9][10] The Q-TWiST method has been used to evaluate therapies for breast carcinoma, [11][12][13][14] human immunodeficiency virus infection, 15,16 rectal carcinoma, 17 melanoma, 18 follicular lymphoma, 19 and multiple myeloma.…”
mentioning
confidence: 99%
“…The literature notes there is wide inter-individual variability in patients' perceptions of chemotherapy, in particular, in the weighing of the survival benefit versus toxicity risk [17][18][19] and in willingness to accept systemic treatment [20]. A key theme is that while choices vary widely, overall patients value even small benefits greatly and judge toxicity as less important in their decision making [1, 17,19,21], suggesting disease experience influences treatment choice.…”
Section: Perceptions Of Lung Cancer Patients: Balancing Risks and Benmentioning
confidence: 99%
“…The degree of survival advantage required to accept chemotherapy has been related to age [5,17,18], although several studies have found no such predictive influence of this characteristic on minimum benefit considered worthwhile by patients [19,20]. A review of determinants of cancer patient preferences concluded that patients are more positive toward adjuvant treatment in the context of larger benefits, less toxicity, personal experience of the particular treatment and having dependents, especially children living at home [22].…”
Section: Perceptions Of Lung Cancer Patients: Balancing Risks and Benmentioning
confidence: 99%